Social Issues: Making them relevant and appropriate to undergraduate student designers - Lofthouse, Vicky (Design and Technology Education: An International Journal, 2013)
Sustainable design education is now considered a core issue for industrial/product design courses, however research has shown that the predominant focus tends to be on environmental issues, as social issues are much harder to tackle. Similarly, social issues are rarely considered in industrial practice. If student designers are to become responsible practitioners, they need to be made aware of social issues that they are in the position to effect. In order to do this it is critical that students are encouraged to consider issues which are relevant to their skill sets and within their sphere of influence. A review of the literature did not reveal a definitive list of social issues for designers to consider. In addition to this the majority of well-known tools used to support sustainable design teaching in UK/Europe, tend to have an ecodesign rather than a sustainable design focus. The few which do exist have their limitations. The paper reports on the findings of an ADM-HEA1 sponsored project. It presents the latest thinking with regards to social issues student designers should be considering. Drawing on a tools analysis and theory review, a set of Social Issues cards are developed and tested to determine their suitability for disseminating social issues to design students. The paper concludes that the tool offers a design oriented perspective of social issues (which has not been provided before) and is a valuable resource for raising awareness about social sustainability in undergraduate design students.